(untitled) (PIONIR: JURNAL PENDIDIKAN, 2025)
Pancasila Education within the Merdeka Curriculum emphasizes the development of students’ critical thinking skills; however, instructional practices at the elementary school level continue to face challenges related to the analytical nature of the content, the potential for conceptual misconceptions particularly in distinguishing the second and fifth principles of Pancasila and the limited variation of learning media and integration of educational technology. Although previous studies have reported the effectiveness of Articulate Storyline and Contextual Teaching and Learning (CTL) when implemented separately, research that systematically integrates both approaches in the context of fourth-grade Pancasila Education, especially for Chapter 4 “Pancasila Dalam Diriku”, remains limited. This study aims to develop Pancasila Education learning media assisted by Articulate Storyline integrated with the CTL model and to examine its feasibility through expert validation involving content, media, and language specialists. The study employed a Research and Development (R&D) approach using the ADDIE model proposed by Branch, implemented up to the formative evaluation stage through expert validation, without conducting classroom implementation or student trials. The developed media, named Pandaku, incorporates trigger videos, interactive content, quizzes with automated feedback, contextual examples, summaries, and reflective activities. The validation results indicate that the media is highly feasible, achieving feasibility percentages of 95.38% (media expert), 96.92% (content expert), and 96% (language expert). Theoretically, this study contributes to the development of instructional design in Pancasila Education by offering a systematic integration of interactive digital media and CTL for value-based content that is prone to misconceptions. Practically, the developed media has the potential to enrich teachers’ instructional resources and support technology-based contextual learning in offline formats. Nevertheless, improvements in students’ critical thinking skills remain an anticipated potential that requires empirical verification through field implementation and effectiveness testing in future studies. Keywords: Pancasila Education, Articulate Storyline, Contextual Model